الجلسة الخاصة بفلسطين للجمعية العامة للأمم المتحدة - حنودة, حسام حسين (جامعة الوادي - University of Eloued, 2023)
تتناول هذه الدراسة موضوع تحويل المشكلة الفلسطينية إلى الأمم المتحدة من أجل التوصل لحل لها في العام 1947، كما تتناول المناقشات التي جرت بين الولايات المتحدة وبريطانيا من أجل عقد جلسة خاصة للجمعية العامة للأمم المتحدة لتشكيل لجنة خاصة لدراسة المشكلة الفلسطينية، وبالإضافة إلى ذلك تتعرض الدراسة للمناقشات التي جرت في داخل الجلسة الخاصة للجمعية العامة، والتوصل إلى قرار بتشكيل اللجنة الخاصة بفلسطين خلال الفترة من28/4/1947وحتى15/5/1947. وقد اعتمدت الدراسة بشكل رئيسي على وثائق الخارجية الأمريكية ووثائق الأمم المتحدة المنشورة . This study, under the title: The Special Session on Palestine of the United Nations General Assembly (28/4/1947-15/5/1947) (a study in light of the United Nations documents and the published documents of the American State Department), deals with the issue of transferring the Palestinian problem to the United Nations in order to reach a It was resolved in the year 1947, after British attempts to reach a solution that satisfies all parties failed, It also deals with the discussions that took place between the United States of America and the British government in order to hold a special session of the United Nations General Assembly in order to form a special committee to study the Palestinian problem. And reaching a decision to form the Special Committee for Palestine during the period from 28/4/1947 to 15/5/1947. The study relied mainly on the documents of the US State Department and the published documents of the United Nations.
مقال
Keywords: الجمعية العامة ; الجلسة الخاصة ; اللجنة الخاصة ; الأمم المتحدة ; فلسطين; United Nations, General Assembly, special committee, Palestine